In vitro recellularization of aorta scaffolds prepared by sonication treatment - Syazwani, N.; Ushida, T.; Azhim, Azran (2015)
Sonication treatment is used in the preparation of bioscaffolds that was able to support repopulation of vascular smooth muscle cells (VSMCs) upon cell-seeding. The aim of this study is to investigate the ability of sonicatedly decellularized tissue to repopulate VSMCs after 6 days of cell-seeding. In this study, sample of aorta tissues are decellularized by sonication treatment in 0.1% and 2% sodium dodecyl sulfate (SDS) detergent for 10 hours. It was followed by washing process with PBS solution for 5 days. Decellularized aorta tissues are then cell seeded with VSMCs by static seeding in 96-well plate containing Dulbecco's Modified Eagle Medium (DMEM) at 37°C. The infiltrations of VSMCs onto decellularized tissues are evaluated by comparison of Hematoxylin-Eosin (H-E) staining at 0 and 6 days of cell-seeding. The histological results of cell-seeding showed that VSMCs are able to infiltrate onto the decellularized tissues. From the results, sonicatedly decellularized tissue treated in 0.1% and 2% SDS, seeded with VSMCs showed infiltration depth of 0.43 mm and 0.35 mm, respectively. Hence, a sonicated decellularized tissue treated with 0.1% and 2% SDS was shown to support the repopulation of VSMCs.